2021
DOI: 10.1089/nsm.2020.0014
|View full text |Cite
|
Sign up to set email alerts
|

On the Consistency between Gene Expression and the Gene Regulatory Network of Corynebacterium glutamicum

Abstract: Background: Transcriptional regulation of gene expression is crucial for the adaptation and survival of bacteria. Regulatory interactions are commonly modeled as Gene Regulatory Networks (GRNs) derived from experiments such as RNA-seq, microarray and ChIP-seq. While the reconstruction of GRNs is fundamental to decipher cellular function, even GRNs of economically important bacteria such as Corynebacterium glutamicum are incomplete. Materials and Methods: Here, we analyzed the predictive power of GRNs if used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The consistency between GRNs and expression data has been previously studied by assuming a causal effect between the expression of the TFs and their target genes (TGs). Recent studies using expression data in E. coli and C. glutamicum have assessed this causal effect by using correlations to show a weak correlation of the known regulatory TF-TG pairs compared to all the possible random pairs as background ( Larsen et al, 2019 ; Parise et al, 2021 ). Moreover, repressor interactions were associated with a positive correlation, rather than the expected negative correlation.…”
Section: Consistency Of Grns: Correlation Does Not Imply Causationmentioning
confidence: 99%
“…The consistency between GRNs and expression data has been previously studied by assuming a causal effect between the expression of the TFs and their target genes (TGs). Recent studies using expression data in E. coli and C. glutamicum have assessed this causal effect by using correlations to show a weak correlation of the known regulatory TF-TG pairs compared to all the possible random pairs as background ( Larsen et al, 2019 ; Parise et al, 2021 ). Moreover, repressor interactions were associated with a positive correlation, rather than the expected negative correlation.…”
Section: Consistency Of Grns: Correlation Does Not Imply Causationmentioning
confidence: 99%
“…Therefore, inference tools based solely on gene expression data tend to also infer non-direct interactions, especially COEX tools (Figure 4C). Perhaps, this consideration may shed light on the search for consistency between GRNs and gene expression data (Larsen et al, 2019; Parise et al, 2021). On the other hand, every tool performs better with the “strong” GS on AUROC (Supplementary figure 12), but this is because of the highly unbalanced positives/negatives ratio (Saito and Rehmsmeier, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Simon Larsen et al performed an in-deep analysis on this matter, their results show that the correlation of pairs of random genes is indistinguishable from those involved in known regulatory interactions in E. coli (Larsen et al, 2019). Doglas Parise et al confirmed the results also on Corynebacterium glutamicum (Parise et al, 2021).…”
Section: Introductionmentioning
confidence: 92%
“…Several studies have shown the interplay between TFs and sRNAs when regulating gene expression by forming regulatory circuits, as reviewed by Beisel and Storz (2010); Nitzan et al (2017), Brosse and Guillier (2018). Furthermore, consistency assessments in E. coli (Larsen et al, 2019) and C. glutamicum (Parise et al, 2021) showed that regulation driven by transcription factors is not able to satisfactorily explain gene expression and suggested other layers of regulation to be integrated into the networks in order to model the complexity of gene expression. Our work contributes to expanding the regulatory landscape of two biotechnological and four pathogenic Corynebacterium species by predicting their sRNA regulatory networks and by integrating them into the corresponding GRNs.…”
Section: Discussionmentioning
confidence: 99%